2015
DOI: 10.20884/1.anprod.2015.17.3.542
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Fermented Complete Feed by Using Sago Residues as Main Source Diet

Abstract: Abstract. Recently, fermentation of low quality feed such as agro industry by products has been widely applied to produce enriched animal feed and improve animal productivity. The purpose of this study was to evaluate in vitro digestibility of fermented complete feed using agro-residues from sago starch processing industries as main source diet. Feed was formulated on the basis of 40% sago residue and mixed with other ingredients (rice brand, coconut meal, bread by product, soybean meal and soybean hulls) to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Therefore, after SSF, pH decreased into slightly acidic in all substrates. NH3 concentration for in vitro protein synthesis was optimum at 5-17.65 mM [22]. The VFA total in this study was sufficient for the fungus growth, indicated by the value is in the range between the normal condition of 60-120 mM [23].…”
Section: Changes In Chemical Compositionmentioning
confidence: 51%
“…Therefore, after SSF, pH decreased into slightly acidic in all substrates. NH3 concentration for in vitro protein synthesis was optimum at 5-17.65 mM [22]. The VFA total in this study was sufficient for the fungus growth, indicated by the value is in the range between the normal condition of 60-120 mM [23].…”
Section: Changes In Chemical Compositionmentioning
confidence: 51%
“…DDM (53.93%) of complete feed was higher than DOM (51.83%) [23]. Organic matter digestibility (72.71%) was higher than dry matter digestibility (70.89%) [24]. Digestibility of organic matter (69.06%) was higher than dry matter (64.52%) [25].…”
Section: Feed Nutrient Contentmentioning
confidence: 99%
“…Hal yang sama dilaporkan pula oleh Ogodo et al (2018), bahwa fermentasi tepung kacang tanah bambara menggunakan bakteri asam laktat secara signifikan mampu meningkatkan kecernaan protein in vitro bahan tersebut dari 68,70 ± 1,73% menjadi 85,24 ± 1,21%. Sedangkan Samadi et al (2015) melaporkan bahwa fermentasi menggunakan kultur bakteri asam laktat komersial SBP mampu meningkatkan kecernaan bahan kering dan bahan organik secara in vitro pada ampas sagu masing-masing dari 68,98% menjadi 70,89% dan dari 70,41% menjadi 72,71%.…”
Section: Hasil Dan Bahasanunclassified